Identification of superior rice donors with enhanced nitrogen use efficiency using a comprehensive multivariate genotype selection strategy - Nguyen Trung Duc; Amooru Harika; Dhandapani Raju; Sudhir Kumar; Renu Pandey; Lekshmy Sathee; Elangovan Alimuthu; Biswabiblap Singh; Chandrapal Vishwakarma; Ranjith Kumar Ellur; Mir Asif Iquebal; Rakesh Pandey; et al. (iScience)
Summary: Improving nitrogen use efficiency (NUE) of rice plants utilizing a few end-of-season traits poses a severe phenotyping bottleneck in exploring the genetic diversity of a large population and genotype selection accuracy. Therefore, a comprehensive multivariate genotype selection strategy was developed to explore maximum genetic variation of 300 diverse rice genotypes and accurately select promising rice donors with enhanced NUE traits on a multi-year (2019, 2021, and 2022) -trait (126 traits) -environment (2) -temporal (5) –location (3) scale. The multi-trait genotype ideotype distance index (MGIDI) ranked Cauvery, Suweon, RPW9-4 (SSI) and BAM3690 (IC463705) as superior NUE genotypes; Moroberekan, PUSA1121 and BAM8315 (Basmati 370) as low NUE genotypes. The multi-location field performance and molecular analysis of key nitrogen assimilatory genes confirmed the outperformance of the Cauvery genotype in terms of possessing efficient N sensing, uptake, transport and assimilation characteristics under N-limited conditions. Phenome-wide multivariate analysis highlights root-shoot plastic response as a key target trait for breeding rice genotypes resilient to N stress conditions.